Lessons Learned from the British Exit from the European Union for Indonesia and the ASEAN Economic Community - Jened, Rahmi; Indahsari, Betharia Noor (Hasanuddin University, 2019)
A soft Brexit scenario will include an implementation period from the day the UK formally leaves the EU to 31 December 2020. During the implementation period, the UK will continue to be functionally treated as an EU member state and remain a party to EU international agreement. Associated with the ASEAN single market, should be considered the readiness of Indonesian regulations and legislations that in sectorial concerns at least three aforementioned legal instruments to be harmonized with the laws of the ASEAN countries. Important findings were shown by the research from the perspectives of business law, especially, capital investment law, intellectual property and international trade law that Brexit has significant impact for EU itself, Indonesia and also AEC.